Evaluation of Sister Chromatid Exchanges and Hypoxanthine guanine phosphoribosyl transferase Gene Mutation Assay in Peripheral Lymphocytes of Workers Exposed to Radiation at Al-Tuwaitha Site: Abdulsahib K. Ali; Amel J. Muttar; Ali H. F.; Abdullah A. K. Haider Y. L. and Khawla A. B. - Ali, Abdulsahib K. (The Iraqi Journal of Veterinary Medicine, 2015)
The present study aims at using the biological techniques in a genotoxicity assessment of low doses of radiation in samples of workers in Al-Tuwaitha site due to decommissioning to radioactive contamination as a result of work. This study included 50 male blood samples, aged 35 - 63 years as well as 35 blood samples from non-smokers and non-alcoholic as control group which included 25 male and 10 female aged 25 -57 years. The endpoints used were sister chromatid exchange (SCE) and hypoxanthine guanine phosphoribosyl transferase (HPRT) mutation assay. The sister chromatid exchange in the human lymphocyte for radiation worker was significantly (P<0.05) higher than in the control group. While the results of mutation for HPRT were non-significant when compared with the control group. In conclusion, the results indicated the possibility of using the changes in sister chromatid exchange as useful biomarkers for the detection of human exposure to ionizing radiation. In conclusion, the increase frequencies of sister chromatid exchange in radiation workers indicate the cumulative effect of low-level chronic exposure to ionizing radiation.